A study of solute - solvent interactions in methanol solutions; potential new sustainable technologies for refinery product upgrading/separating and methanol utilization - Zhang, Z (2017)
The upgrading of fluid catalytic cracking (FCC) gasoline is a significant refinery process which is required to decrease FCC gasoline’s alkenes and organosulfur compounds (OSCs) levels to meet stringent, regulated specifications, whilst maintaining or increasing the octane number. The separation and recovery of alkene contents in gaseous alkene and alkane mixtures produced in the refining process is presently a substantial consumer of both energy and resources. The current processes for these upgrading or separation processes rely heavily upon energy – intensive technologies which require severe conditions and complex procedures, involving the widespread use of hydrogen. In this research, I explore new routes, based on novel and innovative chemistry, to improve the considerable energy consumption and overcome the above disadvantages in current FCC gasoline upgrading and gaseous alkene and alkane separation, and to develop lower cost, less energy-intensive approaches to these significant challenges. The potentially sustainable chemical – methanol – was introduced as the key to fulfil the aim of this research. After studying the microscopic nature of the hydrogen bond interactions between methanol and various hydrocarbons, alternative green and sustainable methanol - based "Extractive Refining/Extractive Distillation" approaches for upgrading the FCC gasoline/separating gaseous alkene and alkane has been developed to replace the conventional processes. In addition, what we define as the lower phase mixtures (LPMs) derived from the "Extractive Refining" processes were themselves utilised as feedstocks in a subsequent catalytic conversion process to yield high quality liquid fuel and other products. Through these processes the LPMs is able to be efficiently converted into high added value products such as gasoline, benzene, toluene, xylenes (BTX) etc.. The feasibilities, mechanisms and advantages of these approaches and processes form the detailed investigations reported in this thesis. At the heart of these new processes is the fundamental issue of hydrogen bond formation between the extractant solvent, methanol, and the primary constituents of FCC gasoline, that need to be extracted, namely light alkenes and organic sulphur compounds, for the latter, typically taken as thiophene in this investigation . The work progresses from the discovery and evaluation of the applied "Extractive Refining/Extractive Distillation" process in FCC gasoline, back through to the fundamental nature, and investigation of the hydrogen bond between solute and solvent, through a variety of physicochemical techniques.